How social innovation can be supported in structurally weak rural regions. Research Report. - Christmann, Gabriela B. (My University, 2020)
In fact, throughout Europe there is an abundance of innovative initiatives to be seen in the countryside, advanced by rural inhabitants, social entrepreneurs, or both in collaboration, and which is here termed "social innovation". To social innovation one can ascribe the potential for meeting the diverse challenges of our society. For some time, political decision makers have also placed hope in social innovation. Early on, the European Commission set itself the target of promoting the empowerment of people and the development of social innovation. There are, however, still many questions about the conditions in which social innovation emerges in rural areas, how its potential can be developed, and what support strategies can be used to assist it. The basis of this Policy Paper is empirical research that tackles these questions. By analysing innovative initiatives in the countryside, the conditions and the actor constellations necessary for their emergence has been reconstructed. The phases through which the processes of innovation are carried out have also been investigated, and critical junctures that could pose a threat to their further progress have been identified, as well as favourable factors. Using the example of failed initiatives, it has been possible to explore what conditions could be adverse, or what obstacles are insurmountable, for an innovative initiative.
Keywords: Strukturschwacher Raum; Ländlicher Raum; Sozialinfrastruktur; Bürgerengagement; Soziales Netzwerk; Regionalentwicklung; Förderungsmöglichkeit; Sozialinnovation